Nellore bulls in Brazilian feedlots can be safely adapted to high-concentrate diets using 14-day restriction and step-up protocols - Parra, F. S. [UNESP]; Ronchesel, J. R. [UNESP]; Martins, C. L. [UNESP]; Perdigão, A. [UNESP]; Pereira, M. C.S. [UNESP]; Millen, D. D. [UNESP]; Arrigoni, M. D.B. [UNESP] (CSIRO Publishing, 2019)
In the present study, the effects of restricted intake of the final finishing diet as a means of dietary adaptation compared with diets increasing in concentrate content (step-up) over periods of 14 and 21 days on growth performance, carcass characteristics, feeding behaviour and rumen morphometrics of Nellore cattle were evaluated. One hundred and twenty 20 months old Nellore bulls (initial BW = 372.2 kg, s.d. = 21.5 kg) were randomly allocated in 24 pens (n = 5 per pen) and fed for 84 days. The study had a completely randomised design with a 2 × 2 factorial arrangement: adaptation using both 14-day and 21-day step-up and restriction protocols. Each treatment was replicated 6 times. One bull per pen was slaughtered (n = 24) at the end of adaptation period to evaluate rumen morphometrics. The remaining bulls (n = 96) were slaughtered at the end of experimental period. Interactions were observed (P < 0.05) for growth performance, feeding behaviour and rumen morphometrics variables. Overall, no protocol or adaptation length main effect (P > 0.05) was observed for any of the growth rate and carcass traits evaluated, except for hot carcass weight (P = 0.03) and dressing percentage (P = 0.04), where bulls adapted for 14 days had heavier carcasses and increased dressing percentage when compared with cattle adapted for 21 days. Cattle adapted for 21 days had a larger (P = 0.005) rumen wall absorptive surface area at the end of adaptation period than those adapted for 14 days however, no differences were detected at the end of finishing period. Thus, Nellore yearling bulls could be adapted for 14 days regardless of the protocol.
Keywords: behaviour; carcass; cattle; papillae; rumen